If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 2s + 7 = 4s + -15 Reorder the terms: 7 + 2s = 4s + -15 Reorder the terms: 7 + 2s = -15 + 4s Solving 7 + 2s = -15 + 4s Solving for variable 's'. Move all terms containing s to the left, all other terms to the right. Add '-4s' to each side of the equation. 7 + 2s + -4s = -15 + 4s + -4s Combine like terms: 2s + -4s = -2s 7 + -2s = -15 + 4s + -4s Combine like terms: 4s + -4s = 0 7 + -2s = -15 + 0 7 + -2s = -15 Add '-7' to each side of the equation. 7 + -7 + -2s = -15 + -7 Combine like terms: 7 + -7 = 0 0 + -2s = -15 + -7 -2s = -15 + -7 Combine like terms: -15 + -7 = -22 -2s = -22 Divide each side by '-2'. s = 11 Simplifying s = 11
| -2a+7=a-87a | | y^2-6*y+7=0 | | 4k^2+18k-18=0 | | y=-0.0741x^2 | | 2k^2+9k-9=0 | | 76+4x= | | 10m^5/3 | | 2x^2+y^2-x-2y+6=0 | | 5555=555 | | Xy+xz=6 | | (5*2x)+(7*3x)=260000 | | 18x+14y=4314 | | Solve(x+1)(x+2)(x+3)(x+5)=144 | | 4t+17=5 | | 3(5t-3)+(4t-8)= | | 5z+2+4z=85 | | 7(4+U)= | | g(x)=af(x+b) | | (2x+5)(3x-5)=90 | | 9x=78x | | (11+4)14=49 | | (3+4)14=49 | | (2+4)14=49 | | 48400(100-10)(100-10)=32400(100+10)(100+10) | | (7+4)14=49 | | 0.72x+1.5+3x=2x+9 | | 48400(100-x)(100-x)=32400(100+x)(100+x) | | 2x*x=16 | | 1.7x*x=16 | | (3x+4)(x-10)+(10-x)(x-8)=0 | | (x+4)14=49 | | 3=m-8 |